Chen’s inequalities for submanifolds in (κ, μ)-contact space form with a semi-symmetric metric connection - Ahmad Asif; Guoqing He; Wanxiao Tang; Peibiao Zhao (Open Mathematics, 2018)
In this paper, we obtain Chen’s inequalities for submanifolds in (κ, μ)-contact space form endowed with a semi-symmetric metric connection.